GE_GERICHTE P/7994/2018 vom 16. Juni 2022 - GE Cour de justice (2022)
LÉSION CORPORELLE SIMPLE;VOIES DE FAIT;INJURE;ENLÈVEMENT(INFRACTION);LÉGITIME DÉFENSE;EXCÈS;ÉTAT DE NÉCESSITÉ | CP.123; CP.126; CP.109; CP.177.al1; CP.183.ch1; CP.15; CP.16; CP.17